PH responsive nanocellulose hydrogel as well as preparation method and application thereof

By combining aldehyde-based cellulose, carboxymethyl chitosan, tannic acid and curcumin-conjugated chitosan in the hydrogel, pH-responsive nanocellulose hydrogels are formed, which solves the problem of the lack of pH responsiveness and antibacterial properties of existing hydrogels in wound dressings, and achieves the slow release of drugs and antibacterial effects in acidic environments.

CN119775595AActive Publication Date: 2025-04-08ANHUI SNOW DRAGON FIBER TECH CO LTD

Patent Information

Application Number
CN202411926901.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Existing hydrogel materials lack pH responsiveness and antibacterial properties in wound dressing applications, making it difficult to effectively release drugs and inhibit bacterial growth in acidic environments.

Method used

The pH-responsive nanocellulose hydrogel was formed by mixing aldehyde-based cellulose nanofibers and carboxymethyl chitosan and adding tanninic acid and curcumin-conjugated chitosan. The hydrogel can achieve slow drug release under acidic conditions and improve antibacterial performance through the synergistic effects of tannin acid and curcumin.

Benefits of technology

The pH-responsive drug release of hydrogels under acidic conditions is achieved, which enhances antibacterial properties, can more effectively promote wound healing and reduce bacterial infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209456110000071
    Figure BDA0005209456110000071
Patent Text Reader

Abstract

The invention discloses pH-responsive nanocellulose hydrogel and a preparation method and application thereof, and belongs to the technical field of hydrogel materials.The preparation method of the hydrogel comprises the following steps that firstly, an aldehyde cellulose nanofiber suspension and a carboxymethyl chitosan solution are mixed and stirred for 1-12 h at the temperature of 25-90 DEG C, and the molar ratio of amino to aldehyde is 1: 5-5: 1; 2, tannic acid and curcumin conjugated chitosan are added into the mixed solution of the aldehyde cellulose nanofibers and the carboxymethyl chitosan, the concentration of the tannic acid is 1-10 mg / mL, the concentration of the curcumin conjugated chitosan is 0.5-5 mg / mL, mixing and stirring are conducted, a cross-linking reaction is conducted, and the pH-responsive nanocellulose hydrogel is obtained. Based on the Schiff base bond effect in the hydrogel, the hydrogel has remarkable pH responsiveness, and by means of the hydrogen bond combination effect and synergistic effect among tannic acid, curcumin and nanocellulose, the hydrogel has good mechanical performance and antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel materials, and specifically relates to a pH-responsive nanocellulose hydrogel and a preparation method and application thereof. Background Art

[0002] The skin is the largest organ in the human body and is a basic barrier that protects the internal tissues of the human body, maintains fluid balance, and prevents the invasion of pathogens. However, the skin is easily damaged by acute trauma, chronic ulcers, and diseases, leading to excessive loss of protein and water, bacterial infection, and even immune system disorders. When the wound is deep into the dermis or subcutaneous tissue, the spontaneous healing process of the wound is difficult. At the same time, bacterial infection also poses a serious threat to wound healing, which can delay collagen synthesis and prolong wound healing time.

[0003] Hydrogels used as wound dressings can maintain a moist environment for wounds, promote cell growth and reduce inflammation, which is beneficial to wound healing. However, hydrogels with a single structure and function still cannot meet the diversified needs in practical applications. In recent years, the molecular design and structural engineering of hydrogels have continued to develop, making them multi-purpose and adjustable. Antibacterial hydrogels can be prepared by adding antibacterial ingredients or drugs to hydrogels, but sudden release of drugs should be prevented to avoid short-lived drug effects or toxicity to normal cells.

[0004] pH is one of the judgment indicators for internal and external diseases. Many disease symptoms are accompanied by significant changes in the pH of the human microenvironment. In addition, based on the difference in microenvironment pH between diseased tissue lesions and normal physiological tissues, hydrogels can be used to respond to the tissue microenvironment and achieve targeted release of drugs.

[0005] Nanocellulose has excellent physical and chemical properties, such as high tensile strength and elastic modulus, high specific surface area, low density, biodegradability and renewability, and is widely used in the field of hydrogels. However, nanocellulose itself does not have antibacterial properties and pH responsiveness. However, pH-sensitive hydrogels have attracted much attention in the field of medical research in recent years. Therefore, the preparation of a nanocellulose hydrogel with pH responsiveness and excellent antibacterial properties can realize its wide application in the field of wound dressings. Summary of the invention

[0006] The purpose of the present invention is to provide a pH-responsive nanocellulose hydrogel and a preparation method and application thereof. The nanocellulose hydrogel prepared by the method not only has pH responsiveness but also has excellent antibacterial properties.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a pH-responsive nanocellulose hydrogel, comprising the following steps:

[0009] Step 1, mixing the aldehyde-modified cellulose nanofiber suspension and the carboxymethyl chitosan solution, stirring at 25-90° C. for 1-12 hours, wherein the molar ratio of the amino group to the aldehyde group is 1:5-5:1;

[0010] Step 2: Add tannic acid and curcumin conjugated chitosan to the mixture of formaldehyded cellulose nanofibers and carboxymethyl chitosan, wherein the concentration of tannic acid is 1-10 mg / mL and the concentration of curcumin conjugated chitosan is 0.5-5 mg / mL, mix and stir to carry out cross-linking reaction, and obtain pH-responsive nanocellulose hydrogel.

[0011] Carboxymethyl chitosan (CMCS) is an important amphoteric polyelectrolyte with significant pH responsiveness. Its molecular structure contains carboxyl and amino groups. In an acidic environment, the swelling rate of carboxymethyl chitosan increases, while it exhibits a smaller swelling rate under neutral or alkaline conditions. In an acidic environment, it can trigger drug release and achieve precise control of drug release.

[0012] The aldehyde-modified cellulose nanofibers contain aldehyde groups, which are cross-linked with the amino groups on carboxymethyl chitosan through Schiff base bonds to construct an injectable hydrogel.

[0013] Tannic acid can improve the mechanical properties of hydrogels by interacting with cellulose and carboxymethyl chitosan through non-covalent bonds. Tannic acid contains a large number of phenolic hydroxyl functional groups, which can provide a variety of interactive binding sites. Tannic acid has antibacterial and antioxidant properties, can remove free radicals in wounds, and promote wound healing.

[0014] Curcumin is a natural polyphenol compound with good anti-inflammatory and antioxidant effects. Studies have shown that curcumin can inhibit the production of a variety of proinflammatory cytokines and inhibit a variety of microorganisms including drug-resistant bacteria. Curcumin and chitosan undergo Schiff base reaction to form curcumin conjugated chitosan, which improves the water solubility of curcumin and enhances its bioavailability. The prepared hydrogel can continuously release curcumin and improve its anti-inflammatory and antioxidant properties.

[0015] Furthermore, the preparation steps of the aldehyded cellulose nanofibers are as follows:

[0016] Step 1, dispersing nanocellulose in water, and pretreating the nanocellulose by TEMPO oxidation method to obtain carboxylated nanocellulose with a surface carboxyl content of 0.8 to 1.8 mmol / g;

[0017] Step 2: Disperse the carboxylated nanocellulose in water at 0.5-1.5 wt%, adjust the pH to 3.0-6.0, add NaIO4 at a molar ratio of NaIO4 to glucose units in the carboxylated nanocellulose of 1:1-3:1, react for 6-48 hours at room temperature in the dark, wash by centrifugation to neutrality after the reaction, and obtain aldehyded cellulose nanofibers after freeze-drying.

[0018] Furthermore, the nanocellulose is prepared by hydrolyzing cotton linter pulp with sulfuric acid and mechanically ball milling.

[0019] Furthermore, the aldehyded cellulose nanofiber suspension is obtained by diluting the aldehyded cellulose nanofibers with water at a mass concentration of 1 to 2%.

[0020] Furthermore, the carboxymethyl chitosan solution is obtained by adding carboxymethyl chitosan to water and stirring and mixing according to a mass concentration of 0.5 to 3%.

[0021] Furthermore, the preparation steps of the curcumin-conjugated chitosan are as follows:

[0022] Curcumin was dissolved in ethanol at a concentration of 0.1-0.2 mol / mL, and chitosan was dissolved in acetic acid solution at 1-2 wt%. The two were mixed at a molar ratio of 1-1.1:2 between curcumin and chitosan. The mixture was stirred evenly and then microwave-heated at 60-80°C for 10-20 min. After the reaction was completed, the mixture was cooled, filtered, and freeze-dried to obtain curcumin-conjugated chitosan.

[0023] Furthermore, the temperature of the cross-linking reaction is 30-40° C., and the reaction time is 3-5 min.

[0024] The present invention also provides a pH-responsive nanocellulose hydrogel, which is prepared by the preparation method as described above.

[0025] The present invention also provides an application of the pH-responsive nanocellulose hydrogel as described above, and the pH-responsive nanocellulose hydrogel can be used to prepare wound dressings.

[0026] Beneficial effects of the present invention:

[0027] The present invention uses natural products with good biocompatibility such as cellulose, chitosan, curcumin, tannic acid, etc. as raw materials to construct a hydrogel with injectability, self-healing and antibacterial properties. Under acidic conditions, the amino group is protonated, the Schiff base bond between the raw materials is broken, and the gap between the hydrogel molecules becomes larger, which can achieve slow release of drugs and has significant pH responsiveness. The hydrogen bonding effect between tannic acid, curcumin and nanocellulose is utilized to improve the mechanical properties of the hydrogel. The prepared hydrogel can better fill irregular wounds while providing physical isolation and a moist environment for the wound, and the synergistic effect of tannic acid and curcumin can play an antibacterial role, promote wound healing, reduce scars, etc. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] Preparation of pH-responsive nanocellulose hydrogels:

[0031] Step 1: prepare nanocellulose by mechanical ball milling of cotton linter pulp, disperse the nanocellulose in water, and pretreat the nanocellulose by TEMPO oxidation to obtain carboxylated nanocellulose with a surface carboxyl content of 0.8 mmol / g.

[0032] Step 2: Disperse the carboxylated nanocellulose in water at 0.5 wt%, adjust the pH to 3.0, add NaIO4 at a molar ratio of NaIO4 to glucose units in the carboxylated nanocellulose of 1:1, react for 6 h at room temperature in the dark, centrifuge and wash until neutral after the reaction, and freeze-dry to obtain aldehyded cellulose nanofibers.

[0033] Step 3, curcumin was dissolved in ethanol at a concentration of 0.1 mol / mL, and chitosan was dissolved in acetic acid solution at 1 wt%, and the two were mixed at a molar ratio of curcumin to chitosan of 1:2, stirred evenly, and then microwaved and reacted at 60°C for 20 min. After the reaction was completed, the mixture was cooled, filtered, and freeze-dried to obtain curcumin-conjugated chitosan.

[0034] Step 4: dilute the aldehyded cellulose nanofibers with water at a mass concentration of 1% to obtain a aldehyded cellulose nanofiber suspension, and add carboxymethyl chitosan with water at a mass concentration of 0.5% and stir to obtain a carboxymethyl chitosan solution.

[0035] Step 5: Mix the aldehyded cellulose nanofiber suspension and the carboxymethyl chitosan solution at a molar ratio of amino group to aldehyde group of 1:5, and stir at 25°C for 12 hours.

[0036] Step 6: Add tannic acid and curcumin conjugated chitosan to the mixture of formaldehyded cellulose nanofibers and carboxymethyl chitosan, with the concentration of tannic acid being 1 mg / mL and the concentration of curcumin conjugated chitosan being 0.5 mg / mL. Mix and stir at 40°C for 3 minutes to perform cross-linking reaction to obtain pH-responsive nanocellulose hydrogel.

[0037] Example 2

[0038] The difference from Example 1 is that in step 5, the molar ratio of amino group to aldehyde group is adjusted to 3:1, and the other steps and conditions are the same as in Example 1.

[0039] Example 3

[0040] The difference from Example 1 is that in step 5, the molar ratio of amino group to aldehyde group is adjusted to 5:1, and the other steps and conditions are the same as in Example 1.

[0041] Example 4

[0042] The difference from Example 2 is that the concentration of tannic acid in step six is ​​6 mg / mL, and the other steps and conditions are the same as Example 2.

[0043] Example 5

[0044] The difference from Example 2 is that the concentration of tannic acid in step six is ​​10 mg / mL, and the other steps and conditions are the same as Example 2.

[0045] Example 6

[0046] The difference from Example 4 is that the concentration of curcumin-conjugated chitosan in step 6 is 3 mg / mL, and the other steps and conditions are the same as Example 4.

[0047] Example 7

[0048] The difference from Example 4 is that the concentration of curcumin-conjugated chitosan in step 6 is 5 mg / mL, and the other steps and conditions are the same as Example 4.

[0049] Comparative Example 1

[0050] The only difference from Example 1 is that tannic acid is not added to the hydrogel, and the other steps and conditions are the same as Example 1.

[0051] Comparative Example 2

[0052] The only difference from Example 1 is that curcumin-conjugated chitosan is not added to the hydrogel, step 3 is omitted, and the other steps and conditions are the same as in Example 1.

[0053] Comparative Example 3

[0054] The only difference from Example 1 is that tannic acid and curcumin-conjugated chitosan are not added to the hydrogel, step three is omitted, and the other steps and conditions are the same as in Example 1.

[0055] Weigh 0.5g of the hydrogel prepared in Example 1 after freeze-drying, and soak it in 500mL of PBS solution with pH=3.2, pH=7.2 and pH=8.2 respectively. After swelling equilibrium, take out the hydrogel sample, wipe the surface moisture with filter paper, measure the wet weight, and calculate the equilibrium swelling degree. Among them, the equilibrium swelling degree at pH=3.2 is 41.50g / g, the equilibrium swelling degree at pH=7.2 is 30.13g / g, and the equilibrium swelling degree at pH=8.2 is 13.27g / g. The swelling degree of the hydrogel under different pH conditions is different, and the swelling degree under acidic conditions is significantly greater than the swelling degree under weak alkaline conditions, which proves that the hydrogel is pH-sensitive and can be used as a targeted pH-responsive drug carrier to continuously and stably deliver drugs. The hydrogel as a wound dressing can accelerate the release of drugs under acidic conditions (such as infected wounds), inhibit bacterial growth, and promote wound healing.

[0056] The hydrogels prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 1:

[0057] Gel formation time determination: The gel time of the hydrogel material was detected using the inversion method at 37°C.

[0058] Antibacterial activity: Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus) were selected to test the antibacterial activity of the sample. Take 100 μL of a 10 6 The bacterial solution with CFU / mL was coated on the LB plate, and then a hydrogel disc with a diameter of 5 mm and a thickness of 1 mm was attached to the LB plate. After culturing in a 37°C incubator for 72 hours, the inhibition rate was calculated based on the size of the inhibition zone.

[0059] Mechanical property testing: After the hydrogel was formed, it was prepared into strips (length 10 cm × width 1 cm × thickness 0.2 cm), and the breaking strength was tested using a universal testing machine at 25°C.

[0060] Table 1

[0061]

[0062] As can be seen from Table 1, in Examples 1 to 3, the molar ratio of amino and aldehyde groups in Example 2 is 3:1, and the gel formation time at this time is the shortest in the examples. The addition of tannic acid and curcumin conjugated chitosan can enhance the antibacterial properties of the hydrogel. In Examples 4 to 7, as the proportion of tannic acid and curcumin conjugated chitosan increases, its antibacterial properties against Escherichia coli and Staphylococcus aureus gradually increase. Combining Example 1 and Comparative Examples 1-3, it can be seen that due to the synergistic effect of tannic acid and curcumin conjugated chitosan, the antibacterial properties of the hydrogel in Example 1 are significantly higher than those in the comparative example. Based on the hydrogen bonding effect between tannic acid and curcumin conjugated chitosan and nanocellulose, the mechanical properties of the examples are better than those of the comparative example.

[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a pH-responsive nanocellulose hydrogel, characterized in that: The following steps are involved: Step 1: mixing the aldehyde-modified cellulose nanofiber suspension and the carboxymethyl chitosan solution, stirring at 25-90° C. for 1-12 hours, wherein the molar ratio of the amino group to the aldehyde group is 1:5-5:1; Step 2: Add tannic acid and curcumin conjugated chitosan to the mixture of formaldehyded cellulose nanofibers and carboxymethyl chitosan, wherein the concentration of tannic acid is 1-10 mg / mL and the concentration of curcumin conjugated chitosan is 0.5-5 mg / mL, mix and stir to carry out cross-linking reaction, and obtain pH-responsive nanocellulose hydrogel.

2. The method for preparing a pH-responsive nanocellulose hydrogel according to claim 1, characterized in that: The preparation steps of the aldehyde-modified cellulose nanofibers are as follows: Step 1, dispersing nanocellulose in water, and pretreating the nanocellulose by TEMPO oxidation method to obtain carboxylated nanocellulose with a surface carboxyl content of 0.8 to 1.8 mmol / g; Step 2: Disperse the carboxylated nanocellulose in water at 0.5-1.5 wt%, adjust the pH to 3.0-6.0, add NaIO4 at a molar ratio of NaIO4 to glucose units in the carboxylated nanocellulose of 1:1-3:1, react for 6-48 hours at room temperature in the dark, wash by centrifugation to neutrality after the reaction, and obtain aldehyded cellulose nanofibers after freeze-drying.

3. The method for preparing a pH-responsive nanocellulose hydrogel according to claim 2, characterized in that: The nanocellulose is prepared by hydrolyzing cotton linter pulp with sulfuric acid and mechanically ball-milling.

4. The method for preparing a pH-responsive nanocellulose hydrogel according to claim 1, characterized in that: The aldehyde-modified cellulose nanofiber suspension is obtained by diluting the aldehyde-modified cellulose nanofiber with water at a mass concentration of 1 to 2%.

5. The method for preparing a pH-responsive nanocellulose hydrogel according to claim 1, characterized in that: The carboxymethyl chitosan solution is obtained by adding carboxymethyl chitosan to water and stirring and mixing according to a mass concentration of 0.5-3%.

6. The method for preparing a pH-responsive nanocellulose hydrogel according to claim 1, characterized in that: The preparation steps of the curcumin conjugated chitosan are as follows: Curcumin was dissolved in ethanol at a concentration of 0.1-0.2 mol / mL, and chitosan was dissolved in acetic acid solution at 1-2 wt%. The two were mixed at a molar ratio of 1-1.1:2 between curcumin and chitosan. The mixture was stirred evenly and then microwave-heated at 60-80°C for 10-20 min. After the reaction was completed, the mixture was cooled, filtered, and freeze-dried to obtain curcumin-conjugated chitosan.

7. The method for preparing a pH-responsive nanocellulose hydrogel according to claim 1, characterized in that: The temperature of the cross-linking reaction is 30-40° C., and the reaction time is 3-5 minutes.

8. A pH-responsive nanocellulose hydrogel, characterized in that The preparation is obtained by the preparation method according to any one of claims 1 to 7.

9. A use of the pH-responsive nanocellulose hydrogel as claimed in claim 8, characterized in that: The pH-responsive nanocellulose hydrogel can be used to prepare wound dressings.

Citation Information

Patent Citations

  • Preparation and application of multi-antibacterial intelligent response hydrogel

    CN118403210A

  • Traditional Chinese medicine micromolecular curcumin photodynamic antibacterial hydrogel and preparation method thereof

    CN118892542A

Cited By

  • Quick-frozen crisp-keeping bamboo shoots and production process thereof

    CN120391632A

  • Nano-cellulose-based antibacterial antioxidant wound indicating hydrogel and preparation method thereof

    CN120815217A

  • A nanocellulose-based antibacterial and antioxidant wound indicating hydrogel and a method of preparing the same

    CN120815217B